Alterações placentárias decorrentes do diabetes tipo 1 em camundongos diabéticos não obesos (NOD) - Santos, Anne Carolline Veríssimo dos (2016)
The non-obese diabetic (NOD) mouse is an experimental model largely used in research due to its development of a phenotypic condition of type 1 Diabetes Mellitus, sharing similarities with the disease in humans. During pregnancy the placenta is a vital organ which develops a diversity of functions that enables the development of a healthy fetus. Thus, the aim of this study was to evaluate the influence of hyperglycemia on placental changes of NOD mice. It was used hyperglycemic NOD female (HNOD) (non- fasting blood glucose test ≥ 270.0 mg/dl, n = 6), normoglycemic NOD female (NNOD) (non- fasting blood glucose test < 180 mg/dl, n = 6) and Balb-c female (n = 8) in this experiment. Placental were collected at 19.5 gestation day (gd). Data analyzed included maternal, fetal and placental weight; placental morphological changes; immunohistochemical expression of CD105, Caspase-3 and Histone-3; and enzyme-linked immunosorbent assay CD105, PGIF-2 and VEGF-A. HNOD females weight was significantly lower at 0.5 gd when compared to NNOD and Balb-c. It was observed a decrease in fetal weight in HNOD when compared to Balb-c (989 ± 68 vs 1290 ± 57 mg, p < 0.05; n = 8). Placental weight was higher in HNOD in relation to NNOD and Balb-c (190 ± 26 vs 130 ± 4 p < 0.0001; 155 ± 8 mg, p < 0.001; n = 8). It was observed an increase of junctional zone (JZ) as well as a decrease of labyrinth (L) of HNOD group, in which it was also noticed nuclear and cytoplasmic alterations on cell populations of both areas when compared to NNOD and Balb-c. It was seen Capase-3 decrease in JZ and an increase of Histone-3 in JZ of HNOD placentas. Regarding the labyrinthin, where fetal-maternal exchange occurs, this group showed CD105 decrease and Histone-3 increase when compared with other groups. In the LZ the CD105 reactivity showed decreased in HNOD (206.9 ± 62.7 m², p < 0.0001) compared to Balb-c (847.9 ± 65.4 m², p < 0.0001) and NNOD (500.2 ± 2.6 m², p < 0.001) whereas in the JZ there was no difference between groups. For Caspase-3, reduced reactivity in the JZ was observed in HNOD (663 ± 107.2 m², p < 0.001) compared to Balb-c (1848 ± 74,3 m², p < 0.001) and NNOD (1239 ± 55.4 m², p < 0.05). In the LZ no difference was verified. For Histone-3, the intensity of reactivity was greater in JZ for HNOD (259.7 ± 20.4 m², p < 0.05) and similar between Balb-c (154.8 ± 30 m², p < 0.05) and NNOD (154.8 ± 16.6 m², p < 0.05). Reduced Histone-3 staining was present in LZ of HNOD (261.5 ± 14.5 m², p < 0.001) compared to Balb-c (653.0 ± 96 m², p < 0.001). The concentration of CD105 were higher in HNOD group in serum (5.28 ± 0.36 x 3.02 ± 0.47 pg/ml, NNOD p < 0.05) and placenta (69.72 ± 0.48 x 56.48 ± 4.5 NNOD p < 0.05 and x Balb-c 50.29 ± 2.4 pg/ml, p < 0.001). The placental PIGF2 concentration increased in HNOD (2.92 ± 0.07 pg/ml, p < 0.001) compared to Balb-c (1.86 ± 0.11 pg/ml, p < 0.001) and NNOD (2.45 ± 0.16 pg/ml, p < 0.05) whereas in the serum there was no difference. The serum and placental VEGFA concentrations were similar in all groups. Hyperglycemia was able to modify both placental regions and cellular structures on this experimental model, which might have altered some cellular events like apoptosis, cellular proliferation and angiogenesis.